Study into the reversal of septic shock with landiolol (beta blockade): STRESS-L Study protocol for a randomised trial. Issue 2 (16th February 2021) - Lall, Ranjit; Mistry, Dipesh; Skilton, Emma; Boota, Nafisa; Regan, Scott; Bion, Julian; Gates, Simon; Gordon, Anthony C; Lord, Janet; McAuley, Daniel Francis; Perkins, Gavin; Singer, Mervyn; et al.
Abstract : Introduction: In 2013, a single-centre study reported the safe use of esmolol in patients with septic shock and tachycardia who required vasopressor therapy for more than 24 hours. Although not powered to detect a change in mortality, marked improvements were seen in survival (adjusted HR, 0.39; 95% CI, 0.26 to 0.59; p<0.001). Beta blockers are one of the most studied groups of drugs but their effect in septic shock is poorly understood; proposed mechanisms include not only the modulation of cardiac function but also immunomodulation. Methods and analysis: STRESS-L is a randomised, open-label, non-blinded clinical trial which is enrolling a total of 340 patients with septic shock as defined by Sepsis-3 consensus definition and a tachycardia (heart rate ≥95 beats per minute (bpm)) after vasopressor treatment of at least 24 hours. Standard randomisation (1:1 ratio) allocates patients to receive usual care (according to international standards) versus usual care and a continuous landiolol infusion to reduce the heart rate between 80 and 94 bpm. The primary endpoint is the mean Sequential Organ Failure Assessment score over 14 days from entry into the trial and while in intensive care unit. Results will inform current clinical practice guidelines. Ethics and dissemination: This trial has clinical trial authorisation from the UK competent authority, the Medicines and Healthcare products Regulatory Agency, and has been approved by the East of England-Essex Research Ethics Committee (reference: 17/EE/0368). The results of the trial will be reported first to trial collaborators. The main report will be drafted by the trial coordinating team, and the final version will be agreed by the Trial Steering Committee before submission for publication, on behalf of the collaboration. Registration: The trial is funded by the National Institute for Health Research Efficacy and Mechanism Evaluation (EME) (Project Number: EME-14/150/85) and registered ISRCTN12600919 and EudraCT: 2017-001785-14.